(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article provides a detailed analysis of current issues of tourism development in Karakalpakstan, current opportunities and future plans. Through investments and innovative approaches in the field of tourism, the region of Karakalpakstan can soon become one of the famous tourist destinations in the world. Also, the article highlights the state of tourism infrastructure in the districts of the Republic of Karakalpakstan by grouping and comparing statistical data, and the influence of the region’s climate on tourism is also studied.